1982
DOI: 10.1111/j.1467-7717.1982.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupant behavior in a six‐storey office building fallowing severe earthquake damage

Abstract: In the Imperial County, California, earthquake of 15th October 1979, the Imperial County Services Building was seriously damaged — and has subsequently been demolished. At the time of the earthquake there were approximately 123 occupants in the six‐storey reinforced concrete building which housed a number of county service departments. This paper investigates occupant behavior in a building subjected to an earthquake, and describes, in detail, what people do during and immediately subsequent to the shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The present study found that only 20 per cent of those at risk evacuated immediately and that this was most common in Hitachi, where the duration of the shaking was much longer than it was in Christchurch. This estimate of immediate evacuation is higher than the 2 per cent reported in Arnold et al (1982) and the 6 per cent reported in Bourque, Russell, and Goltz (1993), but is lower than the 38 per cent reported in Prati, Catufi, and Pietrantoni (2012). The present results are similar to those of Prati, Catufi, and Pietrantoni (2012) in terms of the overall (Christchurch and Hitachi combined) percentage of respondents who took cover: 12 per cent in both studies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The present study found that only 20 per cent of those at risk evacuated immediately and that this was most common in Hitachi, where the duration of the shaking was much longer than it was in Christchurch. This estimate of immediate evacuation is higher than the 2 per cent reported in Arnold et al (1982) and the 6 per cent reported in Bourque, Russell, and Goltz (1993), but is lower than the 38 per cent reported in Prati, Catufi, and Pietrantoni (2012). The present results are similar to those of Prati, Catufi, and Pietrantoni (2012) in terms of the overall (Christchurch and Hitachi combined) percentage of respondents who took cover: 12 per cent in both studies.…”
Section: Discussionsupporting
confidence: 55%
“…One student reported a stampede for the exits from a theatre, and Alexander himself observed people engaged in apparently aimless running from place to place in a major piazza. Arnold et al (1982) report a high level of adaptive response by occupants of an office building during the 1979 Imperial Valley earthquake, which occurred slightly south of the Mexico-United States border. Most people's first reaction to the shaking was to take cover under a desk (36 per cent) or in a doorway (15 per cent), but many others froze in place (37 per cent), and a few immediately evacuated into the main corridor (3 per cent) or out of the building (2 per cent).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies by Prati et al [12] and Lindell et al [13] have built on previous work [14,15,16,17,18,19,20]. Specifically, the Prati et al [12] study of the 2012 Emilia-Romagna MW 6.1 earthquake found that the most common response was to move to another room (42%), followed by evacuating the home (36%), waiting in bed (33%), going downstairs (28%), getting dressed (19%), sheltering in a doorway (14%), sheltering near a supporting wall (14%), and sheltering under a table (2%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data from actual earthquakes around the world also highlight the range of actions that people have taken at the time of shaking, and these data were used to inform the surveys. Such actions have been dependent on the context of each earthquake but include: staying still or motionless (Arnold, Eisner, Durkin, & Whitaker, ; Lindell et al., ; Tokyo Fire Department, ); looking around (Lambie et al., ); holding on to someone or something (Lambie et al., ); taking cover under a doorway, desk, or other furniture (Archea, ; Arnold et al., ; Goltz, Russell, & Bourque, ; Prati, Saccinto, Pietrantoni, & Pérez‐Testor, ); dropping and covering (Lindell et al., ); moving to another location within a building (Johnston et al., ; Lambie et al., ; Prati et al., ); turning off fuel outlets or equipment utilizing fire (Archea & Kobayashi, ; Ohta & Ohashi, ; Takuma, ); and exiting/evacuating buildings (Archea, ; Archea & Kobayashi, ; Lindell et al., ; Ohta & Ohashi, ; Prati et al., ; Takuma, ;). While it is difficult to put exact numbers on the most common actions, it would be fair to say that a significant proportion of people undertake movement during shaking, either to take a few steps to another part of a room/building, or to evacuate.…”
Section: Introductionmentioning
confidence: 99%